Ad hoc mobile wireless networks : - Sarkar, Subir Kumar (Auerbach Publications, 2008)
When developers encounter applications in emergency response and disaster recovery, health care and certain industrial environments chances are good they will choose the simple infrastructures and low demands for central administration of ad hoc mobile wireless networks. Written with the professional in mind and including the latest wireless technologies, this gives readers a solid background in the requirements of such networks along with practical advice for specific applications. Along with a review of the fundamental technologies, the authors, all of them distinguished academics from India, cover the wireless Internet, challenges in research and technology, medium access control layer protocols for ad hoc wireless networks, routing protocols, multicast routing protocols, transport protocols, quality of service issues, energy management systems, mobility models, cross-layer design issues and the most recent applications and developments. This includes very useful illustrations and references for each chapter.